Whoever Pays the Piper Calls the Tune: Kurt Jooss, Public Subsidy, and Private Patronage. (May 2018) - Lidbury, Clare
Abstract : This article discusses how subsidy and patronage from German municipalities, private individuals, and British organisations supported Kurt Jooss's artistic output enabling him to create new work, to have high production values, and to present and disseminate his work in Britain, across Europe, the USA and South America. Working chronologically, consideration is given to how each sponsor and benefactor impacted on Jooss's work, particularly his activities as a theatre/opera director and as a choreographer for Baroque operas and oratorios. It is concluded that without such deliberate sponsorship Jooss's work would have been severely restricted.